Иктктерий гиппарионовый (Ictitherium hipparionum) из мэотических отложений села Черевичного Одесской области - Семенов, Ю.А. (Вестник зоологии, 1975)
Ictitherium hipparionum from the vil. Cherevichnoe belongs to the smallest of the known representatives of the species. By dimensions of the skull and mandible it yields to some samples of I. robustum and has a series of morphological characters indicating the necessity to revise the existing diagnoses of these species.